Promoting sales in e-commerce live streaming: How streamer credibility, attractiveness, and time pressure drive purchase decisions - Pan Meizhen; Lim Ming-Fook; Li Xiaoqing; Brahim Chekima (RSIS International, 2025)
This study examines the factors influencing consumer purchase decisions within the rapidly expanding e-commerce live streaming landscape. Drawing on source credibility theory and perceived value theory, it examines the direct effects of host credibility (encompassing trust, expertise, and attractiveness) and product attractiveness on purchase decisions. Furthermore, it uniquely explores the critical moderating role of time pressure, a defining characteristic of live streaming environments. Empirical analysis confirms that both host credibility and product attractiveness significantly and positively influence viewers' purchase decision. Crucially, the study reveals that time pressure acts as a significant moderator, strengthening the positive relationships between (a) host credibility and purchase decision, and (b) product attractiveness and purchase decision. These findings challenge the assumption of purely rational decision-making in e-commerce, highlighting the potent influence of real-time urgency and product perceptions in interactive, time-constrained live streaming. The research contributes theoretically by integrating temporal pressure into the digital persuasion framework of live commerce and offers practical insights for platforms, brands, and hosts to optimize live streaming strategies. Specifically, it underscores the importance of selecting credible hosts, enhancing product visual appeal, and strategically leveraging time-limited promotions to amplify persuasive impact and drive sales conversion.